Արցախահայ գորգարվեստի յուրացման քաղաքականությունը Ադրբեջանում - Բալայան, Մելանյա (ԱրՊՀ հրատ․)
Стилистические особенности узоров Арцахских ковров выражают армянские традиционные представления о жизни, природе, бесконечности и, в целом, верования армян. Турецкие культурологи утверждают, что искусство армянского ковроткачества имеет “тюркское происхождение”. Однако все их утверждения беспочвенны и преследуют политические цели. The characteristic patterns of the carpets of Artsakh and its stylistic peculiarities reflect the traditional Armenian ritual and cult images of life, nature and eternity. In general the Armenian carpets reflect the belief of the Armenians which is absolutely different from that of the alien Turk-Tatar tribe, their traditions and customs. The Turk experts of culture ascribe “Turkish origin” to the Armenian art of carpet-making. However all their groundless standpoints pursue only political goals.
Keywords: Արցախ; Գորգագործություն; Քաղաքականություն